KEDUDUKAN FIRMA SEBAGAI DEBITUR (TERMOHON) PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG (PKPU) DALAM HUKUM KEPAILITAN (STUDI TERHADAP PUTUSAN MA No. 156 PK/Pdt.Sus/2012) - RONNY ROY FERNANDO (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Sunarmi2. Mahmul Siregar3. T. Keizerina Devi A A firm is an enterprise which does not have any legal entity that is established to run the firm under a collective name as stipulated from Article 16 until Article 35 of KUHD (Commercial Law Code). An enterprise that has legal entity is the one that can be declared bankrupt. As mentioned in the Commercial Court’s Ruling at the Makassar District Court No. 01/PKPU/2012/PN. NIAGA. MKS, it is declared that FIRMA LITHA & CO is bankrupt it then files a request for PK (Review) against this ruling. The ground and argument in the record of the Review filed by Firma Litha & CO is that it does not have any legal entity that it is ended with the Supreme Court’s Ruling No.156 PK/Pdt.Sus/2012 that revokes the Commercial Court’s Ruling at the Makassar District Court No. 01/PKPU/2012/PN. NIAGA. MKS. This thesis discusses the position of the firm that does not have any legal entity in the Bankruptcy Law System in Indonesia as well as the ground of the objection of the Supreme Court to the Firm that files a request for PKPU (Postponement of Obligation to Pay Debt) in the Supreme Court’s Ruling No. 156 PK/Pdt.Sus/2012. This thesis also discusses the liabilities of the associates of the Firm in Indonesian Bankruptcy Law.Keywords: Firm Bankruptcy, Liabilities of Firm Associates